Sebuah Pedagogy Anti-Kekerasan: Membaca Relasi Orang Tua dan Anak melalui Lensa Teori Dekolonial - Matatula, Christy (Theologia in Loco, 2025)
Western colonization presents the domination system of authorities to the marginalized (subaltern). The authorities colonize based on their interest in the subaltern. The model of colonization has an impact on various aspects of life, including the system of education. The system of pedagogy is in charge of various systems, including family, as shown in the relationship between parents and children. Sometimes, parents posit themselves as the authorities and children as the subalterns. In some conditions, its domination has the potential to turn into a kind of verbal abuse that harms children. In response to the issue, I employ postcolonial theory to identify and transform the dominion system of others to an egalitarian system of education. In conclusion, this study aims to revisit the system of education based on decolonial theory as a proposal alternative and solution as Marshall B. Rosenberg proposes on anti-violent communication.